The Role and Constraints of Group Sharia Financing in the Economic Empowerment of Women Customers - Dewi Piyanggara; Novi Puspitasari; Suparman (Optima Science, 2023)
The purpose of this research is to analyse the role and constraints of group sharia financing in women's economic empowerment for BTPN Syariah Bondowoso customers. This research uses a qualitative approach with a case study method. The location of the object of this research is BTPN Syariah Bondowoso group sharia financing customers in Sumbermalang Village, Wringin District, Bondowoso Regency. Researchers used primary data obtained through interviews. The selection of informants was carried out using purposive sampling technique. The results showed that the group sharia financing product at BTPN Syariah Bondowoso has participated in the economic empowerment of underprivileged women customers. The empowerment includes providing financial assistance as business capital, providing training that is useful for increasing customer literacy and abilities, and assistance in managing customer businesses carried out by BTPN Syariah Community Officers (CO). The results also show that the obstacles experienced in the implementation of group sharia financing as an effort to empower the economy are the bad instalment payments among customers. These obstacles are caused by business failure and misuse of funds for consumptive activities.